Бедность, нищета и криминализация общества - Гладкий, В. В. (ISCIENCE, 2017)
Целью статьи является исследование природы и сущности бедности и нищеты, а также влияния этих негативных социально- экономических факторов на криминализацию общества в современной Украине. Поддавая критическому анализу связь бедности, нищеты и преступности, автор формулирует важные теории и закономерности их зависимости и взаимообуславливаемости. Особое внимание уделяется авторской теории «бунта против общества», которая объясняет трансформацию нищего человека в преступника, изначально совершающего преступления в качестве «акта против», а, в дальнейшем – как «акта для». Формулируются актуальные рекомендации для действующей законодательной и исполнительной ветви власти в Украине по противодействию криминализации общества, путём совершенствования политики недопущения дальнейшего расширения и углубления в государстве «социального дна». The purpose of this paper is a research study into the nature and essence of poverty and impoverishment, as well as the impact effect of these negative social and economic factors upon criminalization of the society in the context of today’s Ukraine. For achievement of this objective, special law books (first of all, criminological literature) and fundamental philosophical literature (Aristotle, Engels, Gassendi, Hegel, Pososhkov, Schopenhauer) are being analyzed, and respective latest statistical data are taken into consideration. Providing a critical insight into interrelationships of poverty, impoverishment, and criminalization of society, the author formulates important theoretical positions and views covering consistency of their dependence and mutual influence. Special attention is given to the author’s theory referred to as "rebellion against society", which explains transformation of a poor man into a criminal who commits from the outset criminal acts in the capacity of "an act against" (mainly, against social injustice), and, further down the road, as "an act for" (criminal infringements are aimed at satisfying personal needs and deriving pleasures, then criminal activities are gradually recognized by a crime committer in the capacity of taking pleasure). The paper covers time-sensitive recommendations of vital importance for legislative branch and executive branch authorities in power by means of development and betterment of policy for avoidance of further expansion and deepening of the "social underworld" on the national scale, as well as it calls attention to the fact that ignoring by a state of problems associated with its population impoverishment will irrevocably lead to new social conflicts in various strata of Ukrainian nation that may endanger the territorial integrity of modern Ukraine
Poverty, Impoverishment, and Criminalization of Society.
Keywords: бедность; бунт против общества; криминализация личности; криминализация общества; нищета; преступное удовольствие; преступность; прозерпинаво потрясение; социальная катастрофа; злочинність; бідність; криміналізація суспільства; криміналізація особистості; злочинна насолода; прозерпінаве потрясіння; criminality; criminalization of personality; criminalization of society; impoverishment; guilty pleasure; penury; Proserpina shock; rebellion against society; poverty; social catastrophe; corruption